Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts